A Free Energy Study of the Catalytic Mechanism of Trypanosoma cruzi Trans-Sialidase. From the Michaelis Complex to the Covalent Intermediate() - Pierdominici-Sottile, Gustavo (2011)
Trypanosoma cruzi trans -sialidase (TcTS) is a crucial enzyme for the infection of Trypanosoma cruzi, the protozoa responsible for Chagas’ disease in humans. It catalyzes the transfer of sialic acids from the host’s glycoconjugates to the parasite’s glycoconjugates. Based on kinetic isotope effect (KIE) studies, a strong nucleophilic participation at the transition state could be determined and; recently, elaborate experiments used 2-deoxy-2,3-difluorosialic acid as substrate and were able to trap a long-lived covalent intermediate (CI) during the catalytic mechanism. In this paper, we compute the KIE and address the entire mechanistic pathway of the CI formation step in TcTS using computational tools. Particularly, the free energy results indicate that in the transition state there is a strong nucleophilic participation of Tyr342 and after this, the system collapsed into a stable CI. We find that there is no carbocation intermediate for this reaction. By means of the energy decomposition method, we identify the residues that have the biggest influence on catalysis. This study facilitates the understanding of the catalytic mechanism of TcTS and can serve as a guide for future inhibitor design studies.